2019
DOI: 10.7150/jca.28529
|View full text |Cite
|
Sign up to set email alerts
|

Lower Expression of Gelsolin in Colon Cancer and Its Diagnostic Value in Colon Cancer Patients

Abstract: Colon cancer is one of the most common malignancies causing the majority of cancer-related deaths. Gelsolin (GSN) has been found to be dysregulated in various cancers. However, the secreted GSN in colon cancer remains largely unknown. In the present study, we explored the expression profile of GSN in colon cancer tissues and the diagnostic value of serum GSN in colon cancer. In addition, the effects of secreted GSN in colon cancer cells were studied. We thus found that immunoreactive GSN levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In diabetes, plasma GSN values were shown to decrease by about half in the blood of type II diabetic humans and mice models [33]. In cancer, several studies reported abnormal level of plasma GSN in multiple solid tumors [34]. Our data indicated a strong correlation of plasma GSN and CLEC3B in plasma concentration of patients with diabetes ( Figure 5).…”
Section: Discussionsupporting
confidence: 62%
“…In diabetes, plasma GSN values were shown to decrease by about half in the blood of type II diabetic humans and mice models [33]. In cancer, several studies reported abnormal level of plasma GSN in multiple solid tumors [34]. Our data indicated a strong correlation of plasma GSN and CLEC3B in plasma concentration of patients with diabetes ( Figure 5).…”
Section: Discussionsupporting
confidence: 62%
“…In addition, several reports indicated GSN as a protein affecting human colon cancer and melanoma cell motility. A very recent report demonstrated that GSN is able to inhibit the malignant phenotype of glioblastoma [37][38][39]. Because of its important role in metastatic processes, as well as in different cellular mechanisms and cellular interactions, GSN has been suggested as a potential target for various therapeutic treatments [40].…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as previously described [18]. Notably, c-Jun and COP1 were detected in the western blotting assays using anti-c-Jun and anti-COP1 antibodies, respectively, but not anti-His or anti-Flag antibodies when the overexpression plasmids were used.…”
Section: Western Blot Analysismentioning
confidence: 99%